Carnosine catalyzes the formation of the oligo/polymeric products of methylglyoxal - Weigand, Tim; Singler, Benjamin; Fleming, Thomas; Nawroth, Peter Paul; Thiel, Christian; Garbade, Sven; Wagner, Andreas H.; Hecker, Markus; Yard, Benito A.; Schmitt, Claus P.; Peters, Verena (Cellular physiology and biochemistry, 2018)
BACKGROUND/AIMS: Reactive dicarbonyl compounds, such as methylglyoxal (MG), contribute to diabetic complications. MG-scavenging capacities of carnosine and anserine, which have been shown to mitigate diabetic nephropathy, were evaluated in vitro and in vivo. - METHODS: MG-induced cell toxicity was characterized by MTT and MG-H1-formation, scavenging abilities by Western Blot and NMR spectroscopies, cellular carnosine transport by qPCR and microplate luminescence and carnosine concentration by HPLC. - RESULTS: In vitro, carnosine and anserine dose-dependently reduced N-carboxyethyl lysine (CEL) and advanced glycation end products (AGEs) formation. NMR studies revealed the formation of oligo/polymeric products of MG catalyzed by carnosine or anserine. MG toxicity (0.3-1 mM) was dose-dependent for podocytes, tubular and mesangial cells whereas low MG levels (0.2 mM) resulted in increased cell viability in podocytes (143±13%, p<0.001) and tubular cells (129±3%, p<0.001). Incubation with carnosine/anserine did not reduce MG-induced toxicity, independent of incubation times and across large ranges of MG to carnosine/anserine ratios. Cellular carnosine uptake was low (<0.1% in 20 hours) and cellular carnosine concentrations remained unaffected. The putative carnosine transporter PHT1 along with the taurine transporter (TauT) was expressed in all cell types while PEPT1, PEPT2 and PHT2, also belonging to the proton-coupled oligopeptide transporter (POT) family, were only expressed in tubular cells. - CONCLUSION: While carnosine and anserine catalyze the formation of MG oligo/polymers, the molar ratios required for protection from MG-induced cellular toxicity are not achievable in renal cells. The effect of carnosine in vivo, to mitigate diabetic nephropathy may therefore be independent upon its ability to scavenge MG and/or carnosine is mainly acting extracellularly.
Gesehen am 03.07.2019